Detection of Fusarium-specific T cells in hematologic patients with invasive fusariosis. Issue 3 (March 2017) - Vallerini, Daniela; Forghieri, Fabio; Lagreca, Ivana; Riva, Giovanni; Barozzi, Patrizia; Quadrelli, Chiara; Morselli, Monica; Bresciani, Paola; Cuoghi, Angela; Coluccio, Valeria; Maccaferri, Monica; Paolini, Ambra; et al.
Highlights: Invasive fusariosis (IF) is an emerging mould infection in hematologic patients. Fusarium -specific T cells are significantly higher in IF patients. In disseminated IF, specific T lymphocytes secretes pro-inflammatory cytokines. In pulmonary IF, we documented only the presence of IL10-secriting T cells. Fusarium -specific T cells could discriminate between different fungal pneumonias.